Trade analysis of timber forest products between China and the United States - Zhang, Yuchun (My University, 2021)
Forest products have become a significant part of internationally traded products. United States forestry has achieved sustainable development, with the improvement of forest management and logging systems more and more forest resources are able to be harvested. In addition to meeting their own domestic demands, the wood production of The United States also has a large surplus for export. This paper discusses the factors that influence the trade of timber forest products in China with the United States from two aspects of trade development pattern and trade friction. To look into this information sources such as forest products import and export trade between China and the United States in recent years, data for quantitative analysis, import and export commodity structure, the international market distribution, woody forest products of China import and export trade, and trade development and prospects were acquired. The results show that: The trade scale of China's wood forest products shows a dynamic growth trend, the import and export commodity structure is relatively concentrated, and the international market is mainly distributed in the United States, Japan and other developed economies. With the increasing diversification of timber forest product export markets, forestry enterprises should strengthen international production capacity and co-operation to deal with trade barriers, accelerate the transformation of the forestry industry, and implement fiscal and taxation policies to promote the sustainable development of the forest products trade.
Keywords: Timber and wood products (import and export); Forest products industry; International trade (forestry)